THE REGULATED INTERNET GAMBLING INDUSTRY IN ITALY: BUSINESS MODELS COMPARED - Calvosa, Paolo (European Scientific Journal, ESJ, 2013)
The use of the internet as a direct gambling distribution channel, regulated by Italian legislation in 2006, has introduced a considerable change into the competitive dynamics of the regulated gambling industry in Italy, and has brought about a rapid development in a new business segment, namely that of internet gambling, which in 2012 reached a total amount wagered in gambling of some 15 billion euro and a gross gambling revenue of 749 million euro. The possibility of reaching gamblers through the web has favoured a process of reconfiguration of the sector, which envisages a comparison with the model of the incumbent firms having operated for many years through the physical distribution network, that of specialized on line firms, who operate ‘at a distance’ through the Net. The present work aims at analyzing the development dynamics and competitive logics of the regulated real money internet gambling industry in Italy, by examining the various business models adopted by firms operating in this specific business segment. This work represents a first phase of a course of long-term research which has as its objective the validation of the theses proposed through the study of empirical cases.